PREDICTORS OF SUSTAINED VIROLOGICAL RESPONSE (SVR) TO PEGYLATED INTERFERON ALPHA (PEG-IFN α) AND RIBAVIRIN (RBV) IN PATIENTS WITH CHRONIC HEPATITIS C INFECTED WITH GENOTYPE 1. - Krasimir Antonov; Dejan Jelev; A. Ivanova; Zahariy Krastev (Peytchinski Publishing, 2011)
Objective: The combined PEG-IFN alpha and RBV therapy achieved SVR in 40 - 50% of patients infected with HCV genotype 1. Identification of virological and host paramemeters predicting SVR will be useful to tailor therapy. Methods: 71 patients with chronic HCV genotype 1 infection were treated with PEG-IFN alpha2a and RBV for 12 months. Predictors of SVR were analyzed by using nonparametric correlation test. Results: SVR was found in 57 / 71 of subjects (80,3%). The significant differences in baseline level of HCV RNA, sex, age, baseline ALT and present of liver cirrhosis between the patients with or without SVR were not found. Correlation was not proved between SVR and all these factors when they were analyzed separately. High correlation was found between serum levels of HCV RNA at the end of 3-th month therapy (Early Virological Response) and SVR (r=0,759; p=0,011).Conclusion: The viral response during the first 3 months of PEG-IFN alpha and RBV therapy is the strongest independent predictor among the all baseline viral and host predictive factors for achieving of SVR.